Endovascular therapy yields significantly superior outcomes for large vessel occlusions compared with intravenous thrombolysis: is it time to randomize?. (28th July 2012) - Rai, Ansaar T; Carpenter, Jeffrey S; Raghuram, Karthikram; Roberts, Thomas D; Rodgers, Daniel; Hobbs, Gerald R
Abstract : Background and purpose: We compared outcomes between endovascular (EV) therapy and intravenous (IV) thrombolysis in large vessel strokes. Methods: 223 patients who had received either IV (n=100) or EV (n=123) therapy were analyzed. Only patients with strokes involving the internal carotid artery terminus (ICA-T, n=45), the middle cerebral artery (M1, n=107) or the bifurcation branches (M2, n=71) were included. The primary endpoint was 3 month outcome based on the modified Rankin Scale (mRS) score, good-outcome defined as mRS ≤2. Results: The good outcome was 44.7% in the EV group and 26% in the IV group (p=0.003, OR 2.3, 95% CI 1.3 to 4.1). There was no difference in mortality or hemorrhage. For ICA-T occlusions, the good outcome was 27.6% in the EV and 0% in the IV group (p=0.004); for M1 occlusions, 40.6% in the EV versus 10.5% in the IV group (p=0.0006, OR 5.8, 95% CI 1.9 to 18.2); and for M2 occlusions, 76% in the EV versus 47.8% in the IV group (p=0.01, OR 3.5, 95% CI 1.2 to 10.2). For M1 occlusions, the death rate was 27.5% for the EV compared with 57.9% for the IV group (p=0.002, OR 3.6, 95% CI 1.6 to 8.3) with no difference observed in mortality for ICA-T or M2 occlusions. In the univariate analysis, age, National Institutes of Health Stroke Scale score and occlusion site were significant predictors of outcome and mortality (p<0.0001 for all). In the multivariable analysis, EV therapy (p=0.0004, OR 3.9, 95% CI 1.8 to 9) and younger age (p<0.0001, OR 0.96, 95% CI 0.9 to 0.98) were significant independent predictors of good outcome. Conclusions: There are significantly higher odds of a favorable outcome with EV compared with IV therapy for large vessel strokes. The data support the rationale of a randomized trial for large vessel occlusions.